Pelatihan Peramalan Bisnis Bagi Pemuda Dan Pemudi Desa Muara Aman Kabupateng Lebong - Putra, Muhammad Bima Eka; Sitinjak , Roki Andreasta; Harianto , Edi (Universitas Dehasen Bengkulu, 2021)
The Business Forecasting Training for Young Men and Women of Muara Aman Village, Lebong Regency is an initiative that aims to improve the skills and knowledge of young people in rural areas regarding business management. With a focus on introducing business forecasting concepts, techniques, and applications, the training aims to provide participants with a deep understanding of how to conduct accurate and effective business forecasting. Through various learning methods, such as lectures, discussions and case studies, participants were given the opportunity to develop practical skills in applying forecasting techniques in their own business context. In addition, the training also encourages collaboration between participants and builds local business networks, with the hope that it will create new opportunities and support sustainable local economic growth in Muara Aman Village and beyond. As such, this training has the potential to be the first step in driving economic development in rural areas and improving the welfare of the village's younger generation.